Legislative framework for sediment management in the United States - P. A. Garcia-Chevesich; S. L. Jones; J. M. Daniels; R. Valdés-Pineda; H. Venegas-Quiñones; R. Pizarro (Ingeniería del Agua)
Sediment erosion is a serious issue, with approximately 75 billion tons of soil is eroded annually around the world (Pimentel and Kounang, 1998). Although erosion is a natural process, it can accelerate due to human activity and land use changes. Increasing soil erosion beyond its natural threshold can result in significant environmental degradation and decreased economic productivity. Implementing sediment management laws and practices is critical to significantly decrease soil erosion and preserve environmental resources. In the United States, there is a comprehensive system of laws and regulations at national, state, county, and city level that govern erosion and sediment control. The laws and voluntary incentives outlined in our paper have significantly reduced the negative impacts of sediment carried in urban and storm-generated runoff, have reduced chemical and biological pollutants in sediment transported in aquatic ecosystems, and have improved the air quality in several cities with air pollution problems. Having a multi-faceted approach to monitoring erosion and improving soil management is important for a healthy, productive environment and economy.